Environmental justice implications of urban tree cover in Miami-Dade County, Florida (2011)
The social, environmental, and economic benefits of urban trees can mitigate many negative aspects of the built environment. As such, disparities in the benefits of tree cover as a result of class or racial segregation represent an environmental injustice. Quantifying the ecosystem services of urban tree cover is increasingly being used to advocate urban greening and sustainability programs. Although some cities have instituted programs promoting tree planting on public property, these programs most often take place in the context of promoting sustainability rather than addressing structural inequities in the built environment. Using field and U.S. Census data, computer modeling, and online resources, this study analyzed variables such as urban forest cover, diversity of trees, and tree condition among White, African American, and Hispanic areas in Miami-Dade County. We then use these results to quantify two key ecosystem services from urban trees and discuss how their provision can be inequitable. This might be due to a failure to first address structural inequities that have been recognized by the environmental justice movement.